2012
DOI: 10.5194/acp-12-10161-2012
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical properties of the regional mixed layer of Mexico's Megapolis Part II: evaluation of measured and modeled trace gases and particle size distributions

Abstract: Abstract. This study extends the work of Baumgardner et al. (2009) in which measurements of trace gases and particles, at a remote, high altitude mountain site, 60 km from Mexico City were analyzed with respect to the origin of the air masses. In the current evaluation, the temperature, water vapor mixing ratio (WMR), ozone (O 3 ), carbon monoxide (CO), sulfur dioxide (SO 2 ) and acyl peroxy nitrate (APN) are simulated with the WRF-Chem chemical transport model and compared with the measurements at the mountai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Lauer et al, 2005;Ochoa et al, 2012;Zhao et al, 2013;Righi et al, 2013), we are confident that MADE3 is also suitable for use with EMAC. Considering the similar results obtained with MADE3 and MADE in the box model test case that was drawn from an actual 3-D model run, we expect similar performance for MADE3 in the 3-D model as well.…”
Section: Discussionmentioning
confidence: 99%
“…Lauer et al, 2005;Ochoa et al, 2012;Zhao et al, 2013;Righi et al, 2013), we are confident that MADE3 is also suitable for use with EMAC. Considering the similar results obtained with MADE3 and MADE in the box model test case that was drawn from an actual 3-D model run, we expect similar performance for MADE3 in the 3-D model as well.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, since MADE has been extensively and successfully evaluated as part of different AC-GCMs and chemistry transport models (e.g. Lauer et al, 2005;Ochoa et al, 2012;Zhao et al, 2013;Righi et al, 2013), we are confident that MADE3 is also suitable for use with EMAC. Considering the similar results obtained with MADE3 and MADE in the box model test case that was drawn from an actual 3-D model run, we expect similar performance for MADE3 in the 3-D model as well.…”
Section: Discussionmentioning
confidence: 97%
“…Global model simulations have indicated that the emissions from ocean ship traffic may be one of the largest contributors to the anthropogenic aerosol forcing (Lauer et al, 2007(Lauer et al, , 2009Righi et al, 2011Righi et al, , 2013Olivié et al, 2012;Peters et al, , 2013. That contribution is mainly caused by the sulfur in the ship exhaust plumes that leads to the Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%